Establishment and culture of mouse oviductal organoids and isolation and characterization of their secreted extracellular vesicles - Riley E. Thompson-Brandhagen; Mindy A. Meyers; Richard B. McCosh; Fiona K. Hollinshead (PLoS ONE, 2025)
Oviductal (fallopian tube) cell cultures are widely used to improve understanding of oviductal pathophysiology and to improve sperm and embryo quality via co-culture. One type of oviductal cell culture is organoids, a three-dimensional cell culture that can mimic the oviduct in vitro long-term (months). Because organoids maintain their structure and function similar to in vivo , their secretions tend to be more similar to in vivo cellular products. One of these organoid secretions includes extracellular vesicles (EVs), which are bioactive nanoparticles secreted by cells for intercellular communication. Here we report a protocol for isolation of mouse oviducts, establishment and long-term culture of mouse oviductal organoids, and isolation and characterization of the EVs secreted by mouse oviductal organoids. This lab protocol can be used for research of oviductal physiology and pathology and improvement of assisted reproductive technologies.